Análisis de seguridad en redes de IoT- caso LoRaWAN - González Guachisaca, Alvaro Fabian (2024)
In the current era of digital connectivity, the widespread deployment of devices of Internet of the things (IoT)it has significantly boosted operational efficiency and service improvement in various sectors. However, this rapid increase in interconnection has also introduced critical security challenges, in low-energy and long-range networks, such as LoRaWAN. This project captures questions about specific vulnerabilities in the LoRaWAN link layer, the impact of attacks on network availability, the current state of security measures implemented and the effectiveness of key management and device authentication. By getting answers to these questions, you will contribute to the development of more robust security strategies and practices for the deployment of LoRaWAN networks in IoT environments. The relevance of this project lies in its ability to analyze current security on LoRaWAN- based IoT infrastructures, showing its strengths and weaknesses in data integrity and guiding decision-making for adequate privacy protection in a context of increasing dependence on connectivity and automation. In addition, the results of this analysis could inform designers, developers and policymakers about best security practices for future LoRaWAN network deployments and, by extension, for the safe development of IoT applications in general. Words: LoRa, LoRaWAN, Security, Wireless Networks.